2017
DOI: 10.1002/sim.7230
|View full text |Cite
|
Sign up to set email alerts
|

Identification of treatment responders based on multiple longitudinal outcomes with applications to multiple sclerosis patients

Abstract: Identification of treatment responders is a challenge in comparative studies where treatment efficacy is measured by multiple longitudinally collected continuous and count outcomes. Existing procedures often identify responders on the basis of only a single outcome. We propose a novel multiple longitudinal outcome mixture model that assumes that, conditionally on a cluster label, each longitudinal outcome is from a generalized linear mixed effect model. We utilize a Monte Carlo expectation-maximization algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Some researchers propose modeling placebo response using a single continuous distribution while modeling treatment response as a mixture distribution. 62,63 This approach is based on the assumption that the distribution of potential outcomes for participants assigned to treatment who will not respond to the active treatment is equivalent to the distribution of potential outcomes for participants assigned to placebo. Applying these model assumptions in studies where large responses to placebo are observed may lead to complications in distinguishing between participants who respond to treatment and those who did not respond to treatment.…”
Section: Placebo Response As a Continuous Characteristicmentioning
confidence: 99%
“…Some researchers propose modeling placebo response using a single continuous distribution while modeling treatment response as a mixture distribution. 62,63 This approach is based on the assumption that the distribution of potential outcomes for participants assigned to treatment who will not respond to the active treatment is equivalent to the distribution of potential outcomes for participants assigned to placebo. Applying these model assumptions in studies where large responses to placebo are observed may lead to complications in distinguishing between participants who respond to treatment and those who did not respond to treatment.…”
Section: Placebo Response As a Continuous Characteristicmentioning
confidence: 99%
“…[4][5][6][7] In epidemiology, increased interest in placebo partly arises from concerns that large placebo effects may mask true clinical effects and bias results. 2 Such concerns have led to a wave of research, alternative study designs [8][9][10][11][12][13] and statistical methods, [14][15][16][17][18][19][20][21] focused on assessing and controlling placebo effects.…”
Section: Introductionmentioning
confidence: 99%